Anatomical structure, and expression of CCL4 and CCL13-like during the development of maxillary barbel in Paramisgurnus dabryanus. (2nd January 2019) - Tan, Kianann; Geng, Ruijing; Wang, Zhiqiang; Liu, Han; Wang, Weimin
ABSTRACT: Paramisgurnus dabryanus is one of the most economically important fishes in China. Barbels are an essential sensory organ for the food-seeking ability of teleost fish. However, the anatomical structure of the maxillary barbels of P. dabryanus and the molecular basis of their development are unknown. We investigated the anatomical structure of the barbel, and gene expression patterns of two chemokine C-C motif ligands: CCL4 and CCL13-like during the maxillary barbel development using Masson Trichrome staining, light and electron microscopy, and qPCR. Anatomically, the maxillary barbel of P. dabryanus contains taste buds, melanophores, collagen fibers, connective tissue, smooth muscles, nerve bundles, and blood vessels, but does not have skeletal muscles or a skeleton rod. The expression of CCL4 and CCL13-like was weak or non-existent in the early phases of development, but high at the last two studied time-points: 192- and 216-h post-hatching. Results indicated that CCL4 and CCL13-like were related to the development of the maxillary barbel.